Sistem Pakan Otomatis Pada Kolam Lele Sangkuriang Menggunakan Motor Servo dan Wemos D1 R32 - Syaputra Rama Adadio; Endang Retnoningsih; Slamet Raharjo (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2025)
The feeding system in Sangkuriang catfish aquaculture requires regular and appropriate feed distribution to support optimal fish growth. This study develops an automatic feeding system using the Wemos D1 R32 microcontroller integrated with a Load Cell sensor, a servo motor, a DC blower, and the Blynk application for remote operation. The research employed a prototyping method that included system design, hardware assembly, and field testing. The results indicate that the device is capable of performing scheduled feeding via Blynk and distributing feed effectively with a dispersion range of approximately 100 cm. These findings demonstrate that the developed system can support improved and sustainable aquaculture technology in automatic feeding management for Sangkuriang catfish cultivation.